Design and Simulation of Sigma-Delta Fractional-N Frequency Synthesizer for WiMAX - H. T. Ziboon; H.M. Azawi (Engineering and Technology Journal, 2008)
This paper presents a design and simulation of proposed frequency synthesizer whichcan be used for WiMAX. Design parameters for the proposed fractional-N PLLsynthesizer for WiMAX system are either selected from WiMAX standards oraccording to results of analysis for each unit of the proposed system. Differenttechniques for phase noise reduction are discussed. Sigma-delta fractional-Ntechnique is chosen for WiMAX system, since low settling time, spurious level andphase noise can be obtained by using this technique. The simulation result shows thesystem is stable, since the phase margin is greater than 45 degree. The settling time,spurious level and phase noise obtained with this synthesizer are 5.9μs, -90dBc/Hz,and -100dBc/Hz respectively. CppSim program (C++ simulator language) and Matlab(V.7) are used for simulation of ΣΔ fractional-N PLL synthesizer.